Analysis Of The Influence Of Financial Management And Taxation Strategies On The Tax Burden Ratio In The Transportation And Logistics Sector Listed On The Idx In 2019-2023 - Prabangkoro, Resi; Nirarta, IGN Agung; Albart, Nicko (LPPM Universitas PGRI Sumatera Barat, 2023)
This study aims to analyze the influence of financial management and taxation strategies on the tax burden ratio in the transportation and logistics sector listed on the IDX in 2019-2023. The research design used is an associative quantitative approach with a longitudinal design. The population in this study were all companies in the transportation and logistics sector listed on the IDX in 2019-2023. Based on the results of the regression analysis explained in Chapter IV, it can be concluded that financial management and taxation strategies have an important role in determining the tax burden ratio in transportation and logistics sector companies listed on the IDX during the 2019–2023 period. Capital Structure (X1), Tax Planning (X4), Tax Credit Optimization (X5), and Tax Burden Reduction (X6) are proven to have a positive and significant effect on the Tax Burden Ratio (Y), with the contribution of each variable increasing between 17% to 44% to the increase in the tax burden ratio. This finding shows that the more intensive the company is in using debt, carrying out tax planning, maximizing tax credits, and implementing tax burden reduction, the tax burden borne by the company will increase significantly. Meanwhile, Asset Management (X2) and Liquidity Management (X3) do not show a significant effect. This indicates that the effectiveness of asset and liquidity use has not directly affected the tax burden in this sector, perhaps because its contribution is greater to operational efficiency than tax liabilities. The regression model used has also met all classical assumption tests, including normality, autocorrelation, multicollinearity, and homoscedasticity, so that the results of the analysis can be said to be valid and can be used as a basis for strategic decision making.